Business Failure Prediction using Sherrod and Kida Models: Evidence from Banks Listed on Iraqi Stock Exchange (2011 - 2014) - Babela, Islam S. T.; Mohammed, Renas I. (Humanities Journal of University of Zakho, 2016)
Nowadays business environment characterized by different types of risks and relatively high business uncertainty levels. This is because of the changes that have taken place by globalization and liberalization. To avoid these risks, it has been a very important matter for financial institutions to give much more attention to performance evaluation and use advanced tools for early detection of business failure. Therefore, in the financial literature, business failure prediction has been widely studied. From this standpoint, this paper attempts to investigate whether the banks listed on the Iraqi Stock Exchange (ISE) expose to business failure by using Sherrod and Kida models. The population of this paper is restricted to banks listed on the (ISE) from 2011 to 2014. Sixteen banks were selected from the total of twenty three. We entirely relied on secondary data which obtained from financial statements of the selected banks. The study reveals that the exposure of selected banks to the risk of bankruptcy is very low based on Sherrod’s Z-score model. In contrast, the selected banks have serious problems and their exposure to bankruptcy is very high according to Kida’s Z-score model. The study also has concluded that the latter model is unreliable to be applied by banks listed on ISE as its results do not compatible with works of selected banks. The finding of the study can be useful for managers, stockholders, investors and concerned users to visualize the ability of banks’ sustainability.